Mechanical cleansing effect using purple leaf denture cleanser on Candida albicans - Ratri Maya Sitalaksmi; Calista Arin Parahita; Fahmi Ahmad; Tomy Aji Wijaya; Nimas Ulinar Damessa Sinaga; Laitlatul Maghfiroh Syafa’ati (Faculty of Dental Medicine Universitas Airlangga, 2026)
Background: Denture stomatitis is experienced by 65% of denture wearers and is generally caused by Candida albicans colonization on the porous surface of acrylic resin. The use of chemical denture cleansers can increase surface roughness and discoloration of the resin, so a natural alternative is needed. Purple leaf extract (Graptophyllum pictum) contains flavonoids that have the potential to be used as a natural denture cleanser with antifungal activity against Candida albicans. Purpose: This study aims to investigate the antifungal potential of purple leaf extract (G. pictum) in the form of denture cleaning soap that effectively inhibits the growth of C. albicans, the cause of denture stomatitis. Methods: This true experimental study used a post-test-only control group design with three groups: K(-) aquades, K(+) baby soap, and P (50% G. pictum extract soap), each consisting of 9 samples. Acrylic resin plates were brushed for 5 seconds per side, rinsed with PBS, incubated on SDA at 37°C for 24 hours, and the number of C. albicans colonies was counted. Data were analyzed using the Kruskal–Wallis and Mann–Whitney tests (p<0.05). Results: Mean C. albicans growth was 90.55 ± 8,54 (K-), 10.55 ± 1.58 (K+), and 20.22 ± 4.05 (P). Significant differences were found among all groups (p<0.05). Conclusion: Denture cleanser containing G. pictum extract reduced C. albicans growth significantly, the extract shows potential as a natural antifungal ingredient for denture cleansers.